S42 Airway epithelial toll receptor expression in asthma and its relationship to disease severity. (16th November 2010) - Cottey, L; Jayasekera, N; Haitchi, H-M; Green, B; Grainge, C; Howarth, P
Abstract : Introduction: Asthma is classically considered a Th2 mediated disease. However, severe and treatment-resistant disease is more heterogeneous and often associated with airway neutrophil recruitment. This may be related to an altered airway bacterial colonisation. Bacteria express pathogen associated molecular patterns (PAMP's) that are recognised as non-self by pattern recognition receptors (PRRs). These PRRs represent an essential component of the innate immunity and an important family of PPRs are the Toll-like receptors (TLR). These are expressed on a range of innate immune cells including epithelial cells. TLR-1, -2, -4, -5 and -6 are located on the cell surface membrane and respond to bacterial cell wall components. This study has investigated the expression of mRNA for TLR-2, -4 and -5 in airway epithelial cells in asthmatics and healthy volunteers. Methods: Epithelial brushings were obtained from the large central airways at fibre-optic bronchoscopy from 18 healthy non-asthmatic volunteers (8 female and mean age 26 years) and 34 asthmatic volunteers (25 female, mean age 43 years). The asthmatic group comprised 7 non-steroid treated and 27 steroid treated asthmatics. The brushings were placed in Trizol and the RNA subsequently extracted and converted to cDNA, prior to real time TaqMan RT-qPCR analysis for the Toll receptors, TLR2, TLR4 and TLR5, as well as IL-8. Results: Gene expression for TLR-2 (p=0.008) and TLR-4 (p=0.012) was significantly increased within the epithelial brushing sample from the asthmatics compared to the healthy control subjects whilst that for TLR-5 did not differ significantly. Interleukin 8 mRNA was also increased within the epithelial brushing sample in the asthmatics (p=0.007) compared to that in the healthy control subjects. These significant differences from the healthy population were also individually present in both the mild and severe asthmatic groups, with no significant difference being evident between mild and severe asthma. Conclusions: These findings reveal up regulation of epithelial gene expression for members of the Toll receptor family relevant to bacterial responses within the airways. Additionally there is enhanced IL-8 gene expression. These features are indicative of on-going innate immune airway responses in asthma. The relevance of this to clinical disease expression requires understanding.